Evaluatıon Of Covıd-19-Related Knowledge, Attıtudes And Practıces Of Physıcıans Workıng In A Medıcal Faculty Hospıtal: An Onlıne Cross-Sectıonal Study From Turkey - Oguzoncul, Ayse Ferdane; Kurt, Osman; Deveci, Süleyman Erhan (My University, 2020)
Objective: In this study, it was aimed to evaluateCOVID-19-related knowledge, attitudes, and practices(KAP) of the assistant physicians who were taking medical specialty training in a medical faculty hospital.Materials and Methods: We performed this crosssectional study in a university hospital. The universe ofthe survey was composed of all assistant physicians whowere taking medical specialty training in this hospital.Results: A total of 264 physicians who were takingmedical specialty training, involving 137 (51.9%) women,were included in the study. The mean age of the physicians was found to be 29.7±3.5. Besides, 44.3% of theparticipants have attended a course or seminar in theirhospitals regarding COVID-19. The most frequently takenindividual measures by physicians were “frequent handwashing,” “avoiding physical contact,” “not entering thebulk areas,” and “changing clothes first after entering thehome.” The knowledge score of the physicians in theinternal branch and physicians attending a course/seminarregarding COVID-19 was significantly higher than thosein the surgical branch (p=0.001) and those not attending(p=0.028), respectively.Conclusions: As a result, we observed some deficiencies in the attitudes and practices of physicians. In order toprevent the lack in terms of information, training can beplanned to physicians at regular intervals
Keywords: COVID-19; Attitude; practices; knowledge; physician